2017
DOI: 10.5624/isd.2017.47.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various cone-beam computed tomography settings on the detection of recurrent caries under restorations in extracted primary teeth

Abstract: PurposeThe aim of this study was to assess the ex vivo diagnostic ability of 9 different cone-beam computed tomography (CBCT) settings in the detection of recurrent caries under amalgam restorations in primary teeth.Materials and MethodsFifty-two primary teeth were used. Twenty-six teeth had dentine caries and 26 teeth did not have dentine caries. Black class II cavities were prepared and restored with amalgam. In the 26 carious teeth, recurrent caries were left under restorations. The other 26 intact teeth th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The influence of tube current (mA) on diagnosis remains a topic of debate within the dental literature. While some studies have found no significant effect on the identification of secondary caries beneath amalgam fillings in primary teeth, 21 others have noted diagnostic improvements in the detection of root fractures, especially when artifact-producing materials are present. 12 13 …”
Section: Discussionmentioning
confidence: 99%
“…The influence of tube current (mA) on diagnosis remains a topic of debate within the dental literature. While some studies have found no significant effect on the identification of secondary caries beneath amalgam fillings in primary teeth, 21 others have noted diagnostic improvements in the detection of root fractures, especially when artifact-producing materials are present. 12 13 …”
Section: Discussionmentioning
confidence: 99%
“…Recurrent caries under different restorative materials are a major cause of the failure and replacement of restorations [ 1 , 2 ]. Although accurate diagnosis of these caries can lead to successful treatment outcomes, it remains a challenging step for clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Although accurate diagnosis of these caries can lead to successful treatment outcomes, it remains a challenging step for clinicians. To provide better detection, visual and radiographic examinations accompanied by other diagnostic methods play a crucial role in treatment planning [ 1 , 3 ]. For these purposes and considering the high prevalence of recurrent caries, periapical and bitewing radiographs are the most common imaging modalities in clinical dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent caries is once in a while observed on occlusal surfaces of the teeth that those edges are effortlessly cleaned. Strikingly, around 50 to 60% of restorations are supplanted on account of a determination of recurrent caries [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The quick improvement of innovation has brought forth different advanced dental imaging modalities, including digital intraoral radiography and cone beam computerized tomography (CBCT) scanners. CBCT has made storming in maxillofacial imaging, encouraging the progress of dental determination from 2D to 3D pictures and extending the part of imaging from finding to imaging guidance of operative and surgical systems by utilization of outsider programming [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%